Lutheranism and the Nordic Welfare States in Comparison - Markkola, Pirjo (A journal of church and state, 2014)
Lutheranism is a dominant feature of the Scandinavian countries or, as they are known in the European context, the Nordic countries—Denmark, Finland, Iceland, N